Spaces of democracy : geographical perspectives on citizenship, participation and representation - Barnett, Clive; Low, Murray (SAGE, 2004)
In an historically unprecedented way, democracy is now increasingly seen as a universal model of legitimate rule. Spaces of Democracy addresses the key question: How can democracy be understood in theory and in practise? In three thematically organised sections, Spaces of Democracy uses a critical geographical imagination (informed by thinking on space, place, and scale) to interrogate the latest work in democratic theory.
Keywords: Political participation.; Democracy.; Citizenship.; Democracy; Participation politique.; Démocratie.; Nationalité.; Citoyenneté.; democracy.; citizenship.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; Citizenship; Political participation; Democratie.; Ruimtelijke aspecten.; Politieke geografie.; Aspect géographique.; Citoyenneté; Gouvernement représentatif.; Spaces; Spaces.